A Comparative Study Of Malaysian And Philippine Folk Literature. - Yaapar, Md Salleh (1977)
Although Malaysians and Filipinos have the same racial origins, so far no comparative study has been carried out on Malaysian and Philippine literature. This study is, therefore, an attempt to "f i l l this need although its scope is limited only to folk literature. The main aim is to explore and compare the folk literature of the two countries and peoples in terms of content, forms or styles, and functions.